THE ROLE OF INFORMATION TECHNOLOGY THROUGH MODERATING COMPETITION INTENSITY IN IMPROVING THE INNOVATION PERFORMANCE OF MSME ACTORS - Sasmita, Hilda Ayu; Sudarnice, Sudarnice; Phradiansah, Phradiansah (PT. Sangadji Media Publishing, 2024)
The purpose of this study was to determine: (1) The influence of IT on the innovation performance of MSME actors in culinary tourism MSME actors in Kolaka Regency. (2) The Role of Competition Intensity in Strengthening IT in Improving the Innovation Performance of MSME Actors in Culinary Tourism in Kolaka Regency. This study uses a quantitative method approach. The population in this study were all culinary tourism MSME actors in Kolaka Regency. While the sample in this study amounted to 32 MSME actors. Testing of the research instrument used validity and reliability tests with SPSS 25.0. The data analysis technique used in this study was a measurement model and structural model testing using Smart PLS 3.0. Based on the results of the study, it is known that there is a positive and significant influence between the IT variable and the innovation performance of MSME actors, as indicated by the t-statistic of 4.898 with a p-value of 0.024. Meanwhile, the moderation of competition intensity is not able to strengthen the IT variable in improving innovation performance as indicated by the t-statistic of 0.022 with a P-value of 0.994. It can be concluded that most MSME actors in culinary tourism in Kolaka Regency have used IT in carrying out innovation performance. However, in culinary tourism in Kolaka Regency, there is no feeling of competition intensity with the use of IT in improving the performance of MSME innovation actors.